Pelatihan Perancangan Model Bisnis Pada Siswa Madrasah Aliyah Kabupaten Majene, Sulawesi Barat - Ashdaq, Muhammad (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
Generation z is the future generation who is expected to have the skills and understanding to face future economic challenges. Entrepreneurship creation is a government program to prepare the younger generation to face competition. One of the problems faced by the younger generation is entrepreneurial knowledge and developing the right business model. This Community Partnership Program (PKM) aims to help partners produce graduates who have an entrepreneurial spirit and the ability to develop business models with the help of the business model canvas tool. The partner in this activity was MAN 1 Majene, West Sulawesi with twenty students participating in the activity. Activities are carried out in the form of training using lecture, mentoring, discussion and practice methods. The results of the activities achieved are (a) Partners have entrepreneurial competence and the ability to use business model canvas tools, (b) Partners gain literacy in developing an entrepreneurial spirit, (c) Partners gain experience analyzing business models with the help of business model canvas tools.